Pengaruh Kebijakan Deviden dan Keputusan Investasi Terhadap Nilai Perusahaan pada Pt Sumber Alfaria Trijaya Tbk di Bursa Efek Indonesia - M. Alif Akbar; Nurul Huda; Nurhayati (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of dividend policy and investment decisions on firm value at PT Sumber Alfaria Trijaya Tbk, which is listed on the Indonesia Stock Exchange during the 2014–2025 period. This research employed a quantitative approach with an associative-causal design. The data used were secondary data obtained from the company's annual financial reports and official publications of the Indonesia Stock Exchange. The sample was selected using a purposive sampling technique with an observation period of 12 years. The independent variables consisted of dividend policy, proxied by the Dividend Payout Ratio (DPR), and investment decisions, proxied by the Price Earning Ratio (PER), while the dependent variable was firm value, proxied by the Price to Book Value (PBV). Data analysis was conducted using multiple linear regression with the assistance of SPSS software through classical assumption tests, coefficient of determination, t-tests, and F-tests. The results indicate that, partially, dividend policy has no significant effect on firm value, with a significance value of 0.593. Investment decisions also have no significant effect on firm value, with a significance value of 0.971. Simultaneously, dividend policy and investment decisions do not significantly affect firm value, with a significance value of 0.805. The coefficient of determination (R²) of 0.047 indicates that the research variables explain only 4.7% of the variation in firm value, while the remaining 95.3% is influenced by other factors outside the research model.